2013
DOI: 10.1021/la401929v
|View full text |Cite
|
Sign up to set email alerts
|

β-Amino Acid and Amino-Alcohol Conjugation of a Nonsteroidal Anti-Inflammatory Drug (NSAID) Imparts Hydrogelation Displaying Remarkable Biostability, Biocompatibility, and Anti-Inflammatory Properties

Abstract: A well-known nonsteroidal anti-inflammatory drug (NSAID), namely, naproxen (Np), was conjugated with β-alanine and various combinations of amino alcohols and l-alanine. Quite a few bioconjugates, thus synthesized, were capable of gelling pure water, NaCl solution (0.9 wt %), and phosphate-buffered saline (PBS) (pH 7.4). The hydrogels were characterized by rheology and electron microscopy. Hydrogelation was probed by FT-IR and temperature-variable (1)H NMR studies. Single-crystal X-ray diffraction (SXRD) of a n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 63 publications
0
31
0
Order By: Relevance
“…Based on their IC 50 values, except 3, rest of the derivatives were found to have a better killing property compared to their parent compound naproxen sodium (NS). It is of note that although 1 and 2 could exhibit better killing properties (IC 50  ~ 2 mM and ~3 mM, respectively) against the cancer cell lines, they also proved to be cytotoxic against the mouse macrophage cell line RAW 264.7 [13]. Because macrophages serve as the first line of defense during tumor establishment [16], a drug molecule with little to no toxic effect against macrophages would be advantageous.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Based on their IC 50 values, except 3, rest of the derivatives were found to have a better killing property compared to their parent compound naproxen sodium (NS). It is of note that although 1 and 2 could exhibit better killing properties (IC 50  ~ 2 mM and ~3 mM, respectively) against the cancer cell lines, they also proved to be cytotoxic against the mouse macrophage cell line RAW 264.7 [13]. Because macrophages serve as the first line of defense during tumor establishment [16], a drug molecule with little to no toxic effect against macrophages would be advantageous.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, we have showed that 4 can inhibit PGE 2 synthesis and delay tumor cell migration ( in vitro ). Since the derivative 4 is capable of forming hydrogel at room temperature [13] it can also be employed as the hydrogel drug-delivery system [23] for sustained release of the anti-cancer agent. However, it is also important to note the difference in the IC 50 vales of 4 against p53 wild type MCF-7 (~3 mM) and p53 null MDA-MB-231 (~6 mM) cells.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Through hydrolysis of the hydrazone bond, Nb was released from the PA gel over the course of a month. Other drugs, including naproxen, dexamethasone, and fenoprofen have also been released from PA gels using cleavable linkers to achieve long-term and localized release [148][149][150][151].…”
Section: Peptide Amphiphilesmentioning
confidence: 99%